2014
DOI: 10.3892/ijo.2014.2546
|View full text |Cite
|
Sign up to set email alerts
|

Torilis japonica extract, a new potential EMT suppressor agent by regulation of EGFR signaling pathways

Abstract: Abnormal metastasis of carcinoma is associated with the loss of epithelial features and the acquisition of a mesenchymal phenotype. The stimulation of cells with epidermal growth factor (EGF) resulted in morphological changes and induced epithelial-mesenchymal transition (EMT). EGF stimulation resulted in increased mobility along with upregulated actin polarization related proteins, E-cadherin regulators and the mesenchymal markers. Treatment with Torilis japonica extract (TJE) along with stimulation by EGF pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Previously, we found that ethanol extracts from the fruit of Torilis japonica arrested abnormal metastasis through regulation of the EGFR signaling pathway in MCF-7 breast cancer cells (27). In this study, we focused on the effects of TJE on the induction of apoptosis through alterations in the mitochondrial membrane potential in colorectal cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we found that ethanol extracts from the fruit of Torilis japonica arrested abnormal metastasis through regulation of the EGFR signaling pathway in MCF-7 breast cancer cells (27). In this study, we focused on the effects of TJE on the induction of apoptosis through alterations in the mitochondrial membrane potential in colorectal cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, there has been an increased interest in the effect of compounds extracted from natural sources on the prevention and treatment of colorectal cancer. Such compounds induce apoptosis and arrest metastasis through the regulation of intracellular signaling in cancer cells (27)(28)(29)(30)(31)(32)(33). Many researchers have identified food extracts that have been used in cancer chemotherapy experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, to inhibit abnormal growth and metastasis of cancer cells, it is very important to find a target substance capable of inhibiting the EGFR activation. Recently, we discovered a novel substance that can inhibit the abnormal metastasis of MCF-7 breast cancer cells by targeting EGFR (17).…”
Section: Introductionmentioning
confidence: 99%
“…The fruits of Torilis japonica (TJ) is 'Sa-Sang-Ja', which is traditional medical herbs prescribed as anti-fungal, anti-allergenic, antibacterial and sedative agent 30) . In addition, several studies have demonstrated that TJ possess anti-inflammatory 31) , anti-angiogenic 32) , anti-invasive 33) , and anti-microbial 34) effects.…”
Section: Binding Of An Antigen By Fcεri-bound Specificmentioning
confidence: 99%